A Combinational Strategy for Effective Heterologous Production of Functional Human Lysozyme in Pichia pastoris - He, Huahua; Wu, Shijie; Mei, Meng; Ning, Jiali; Li, Chaoyin; Ma, Lixin; Zhang, Guimin; Yi, Li (Frontiers in Bioengineering and Biotechnology, 2020)
Human lysozyme (hLYZ), known as its bacteriolytic activity, is widely applied in the food and pharmaceutical industries as an antimicrobial agent. However, its extensive application was limited by its low large-scale production efficiency. In this study, a combinational method of integrating codon optimization, multiple gene copies, and ER molecular chaperones co-expression was developed to improve heterologous production of hLYZ in Pichia pastoris GS115. Our results showed that increasing copy number of the optimized hLYZ gene in P. pastoris could enhance its secretory production level up to 1.57-fold. The recombinant opt-hLYZ-6C strain that contains 6 copies of opt-hLYZ gene exhibited the highest mRNA transcription levels, giving the highest production of 0.22 ± 0.02 mg/mL hLYZ in the medium supernatant with bacteriolytic activity of 14680 ± 300 U/mL against Microccus lysodeikicus in the shaking flask experiment. Moreover, co-overexpression of ER retention molecular chaperones, such as Pdi1 or Ero1, in the recombinant opt-hLYZ-6C strain both presented positive effects on the secretory production of hLYZ. Our further characterization indicated that tandem co-expression of Ero1 and Pdi1 together presented added up effect. The secretory production of hLYZ in the medium supernatant reached 0.34 ± 0.02 mg/mL of the recombinant opt-hLYZ-6C-EP strain in the shaking flask experiment, with bacteriolytic activity of 21200 ± 400 U/mL. Comparing to the recombinant opt-hLYZ-1C strain, these final improvements were calculated as 2.43-fold and 2.30-fold on secretory protein levels and antibacterial activity, respectively. Finally, the recombinant opt-hLYZ-6C-EP strain was applied for high-density cultivation in 5 L fermenter, in which the secretory yield of hLYZ reached 2.34 ± 0.02 mg/mL in the medium supernatant, with bacteriolytic activity of 1.76 ± 0.02 x 10^5 U/mL against M. lysodeikicus. All these numbers presented the highest heterologous production levels of hLYZ in microbial systems.